Hydrothermal Synthesis and Crystal Structure Based on Benzophenone-2,4’-carboxylate and 1,2-Bis(4-pyridyl)ethane - Zhou, Xiaoshuang (Asian Journal of Chemistry, 2012)
Co-crystallization of benzophenone-2,4'-carboxylate and 1,2-bis(4-pyridyl)ethane was synthesized and characterized by X-ray diffraction at the triclinic, space group P-1 with a = 7.443(5), b = 9.293(10), c = 13.131(5) Å, b = 79.276(5)°, Mr = 363.36, V = 843.1(8) Å3, Dc = 1.431 g/cm3, F(000) = 380 and Z = 2. There are one molecule of benzopenone-2,4'-carboxylate and 1,2-bis(4-pyridyl)ethane in the asymmetric unit. The intermolecular hydrogen bonds are observed in the compound.